The Influence of Organizational Commitment and Job Satisfaction on the Work Ethic of Civil Servants in the Youth, Sports and Tourism Department - Fachri, Helman (Journal of Asian Multicultural Research for Economy and Management Study, 2023)
This research aims to determine the influence of organizational commitment and job satisfaction on the work ethic of Civil Servants at the Youth, Sports and Tourism Service of Kapuas Hulu Regency as an RI-Sarawak Malaysia Border District. This type of research is associative, and the sampling technique used in the research is a total sample, with a total sample of 38 respondents. The analytical tools used in this research are multiple linear regression, multiple correlation coefficient (R), coefficient of determination (R2), F test (Simultaneous Test) and t test (Partial Test). The research results show that the regression equation Ŷ = 1.274 +0.687 (X1) + 0.687 (X2). The multiple correlation coefficient (R) value is 0.852, which means that the relationship between organizational commitment and job satisfaction on the work ethic of Civil Servants at the Kapuas Hulu Regency Youth, Sports and Tourism Service is very strong. The coefficient of determination (R2) value obtained in this research is 0.726, which means that the contribution of the organizational commitment and job satisfaction variables in influencing the rise and fall of the work ethic variable for Civil Servants at the Kapuas Hulu Regency Youth, Sports and Tourism Service is 72.6% and the remainder is 72.6%. 27.4% was influenced by other variables not examined in this research. The results of the F test show that the variables of organizational commitment and job satisfaction simultaneously influence work ethic.